1983
DOI: 10.1021/bi00280a022
|View full text |Cite
|
Sign up to set email alerts
|

Plasma actin depolymerizing factor has both calcium-dependent and calcium-independent effects on actin

Abstract: The effects of pig plasma actin depolymerizing factor (ADF) on both G-actin polymerization and F-actin fragmentation have been examined by using rabbit skeletal muscle actin labeled with N-(1-pyrenyl)iodoacetamide, a sensitive fluorescent probe for monomer to filament interconversion. Fluorescence data have been compared with results obtained by viscometry and by difference absorption measurements at 232 nm. Plasma ADF nucleates actin filament assembly in a Ca2+-dependent manner; actin polymerization rates are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
53
1

Year Published

1985
1985
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(56 citation statements)
references
References 48 publications
2
53
1
Order By: Relevance
“…The regulation of ADF action by Ca2+ may be more complex in a tissue section than in vitro owing to as yet unknown factors which are not present in the purified system. This Ca2+ dependence of ADF action has been reported previously [lo, 15,161, though Harris and Weeds [12] have shown that certain activities of ADF are Ca'+-insensitive. These discrepancies may be in part explained by the use of different techniques to measure the same phenomena.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The regulation of ADF action by Ca2+ may be more complex in a tissue section than in vitro owing to as yet unknown factors which are not present in the purified system. This Ca2+ dependence of ADF action has been reported previously [lo, 15,161, though Harris and Weeds [12] have shown that certain activities of ADF are Ca'+-insensitive. These discrepancies may be in part explained by the use of different techniques to measure the same phenomena.…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, we cannot exclude the possibility that plasma contains two pools of ADF, one Ca2+-sensitive, the other Ca2+-insensitive. Each could be extracted in different amounts by the different purifications procedures which have been used [12] (and this paper). Markey et al [32] have, in fact, purified on a DNase-actin column a 90-kDa protein from platelets, having actin-destabilizing activities some of which are Ca'+-sensitive and some of which are not.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma gelsolin displays both calcium-dependent and calcium-independent effects, and interacts with actin in a polymorphous fashion (49), with each molecule possessing two distinct actin-binding sites (48,(50)(51)(52)(53). At low plasma gelsolin:actin molar ratios, the actions of nucleating actin filament assembly, blocking the fast growing end of the filaments, and severing actin filaments, are all strongly affected by the presence of calcium (46,50,(52)(53)(54).…”
Section: Discussionmentioning
confidence: 99%
“…Over the past 5 years, Ca'+-dependent severing proteins have been identified in a number of non-muscle cells and tissues, including macrophage [2], platelets [3], blood plasma [4], microvillus [5], thyroid [6], Physarum [7,8], and Dictyostefium [9]; however, Ca2+-dependent severing and capping proteins have not been isolated from skeletal muscle.…”
Section: Introductionmentioning
confidence: 99%